Enhanced production of ethanol from enzymatic hydrolysate of microwave-treated wheat straw by statistical optimization and mass balance analysis of bioconversion process. Issue 10 (26th November 2021) - Patel, Amisha; Patel, Harshvadan; Divecha, Jyoti; Shah, Amita R.
Abstract: With a view to develop an efficient bioconversion process from wheat straw to ethanol, the present investigation is aimed at optimizing a separate hydrolysis and fermentation process (SHF) from wheat straw hydrolysate. Enzymatic hydrolysate was obtained using a cocktail of indigenously produced fungal cellulases and commercial cellulase. Ethanol fermentation was carried out using Saccharomyces cerevisiae 3570. The SHF process was optimized by response surface methodology. The variables used were reducing sugar concentration (%), inoculum size (g/L) and fermentation time (h). A well-fitted regression equation with R 2 value of 0.968 and 0.969 was attained for ethanol concentration (g/L) and productivity (g/L/h), respectively. The validation of experimental results showed maximum ethanol concentration and productivity of 32.44 g/L and 0.95 g/L/h, respectively, with a yield of 0.30 g ethanol/g reducing sugar consumed, which was in accordance with the predicted value. After statistical optimization, the ethanol concentration and productivity were enhanced up to 1.13- and 2.38-fold, respectively. Mass balancing of the integrated process showed that maximum ethanol production was 80 g/kg of wheat straw. The present investigation resulted in higher ethanol concentration and productivity despite using milder pretreatment, lower enzyme loadings and lesser inoculum in fermentation as compared to similar investigations reported earlier.